Under siege! : three children at the Civil War battle for Vicksburg - Warren, Andrea (Melanie Kroupa Books, 2009)
Tells the story of Lucy McRae and Willie Lord, survivors of the battle for Vicksburg in 1863, that describes how they lived in caves and underground bunkers as Union artillery bombarded the town for six week; and also tells of young Frederick Grant, son of Ulysses S. Grant, who witnessed the carnage of that battle.